2015
DOI: 10.1126/scisignal.2005769
|View full text |Cite
|
Sign up to set email alerts
|

Temporal proteomics of NGF-TrkA signaling identifies an inhibitory role for the E3 ligase Cbl-b in neuroblastoma cell differentiation

Abstract: SH-SY5Y neuroblastoma cells respond to nerve growth factor (NGF)-mediated activation of the tropomyosin-related kinase A (TrkA) with neurite outgrowth, thereby providing a model to study neuronal differentiation. We performed a time-resolved analysis of NGF-TrkA signaling in neuroblastoma cells using mass spectrometry-based quantitative proteomics. The combination of interactome, phosphoproteome, and proteome data provided temporal insights into the molecular events downstream of NGF binding to TrkA. We showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 81 publications
7
60
1
Order By: Relevance
“…Class I phosphopeptide sites comprise those residues with the highest localization probability for the phospho-group (>0.75); that is, the sum of probabilities of other potential sites is less than 0.25. From more than 2,000 identified and quantified class I phospho-sites, the distribution of phosphoserine (pSer), phosphothreonine (pThr), and phosphotyrosine (pTyr) sites observed in cells transfected with rat or chimeric TrkA was similar to distributions reported previously with cells stimulated with NGF or epidermal growth factor (EGF) (Emdal et al., 2015, Olsen et al., 2006). We next examined the NGF-upregulated phospho-sites and found that significantly more phosphopeptides were upregulated in NGF-treated cells with rat TrkA (361/2,239 [16.8%]) compared to cells with chimeric TrkA (270/2,007 [13.5%]; Figure 4B).…”
Section: Resultssupporting
confidence: 80%
“…Class I phosphopeptide sites comprise those residues with the highest localization probability for the phospho-group (>0.75); that is, the sum of probabilities of other potential sites is less than 0.25. From more than 2,000 identified and quantified class I phospho-sites, the distribution of phosphoserine (pSer), phosphothreonine (pThr), and phosphotyrosine (pTyr) sites observed in cells transfected with rat or chimeric TrkA was similar to distributions reported previously with cells stimulated with NGF or epidermal growth factor (EGF) (Emdal et al., 2015, Olsen et al., 2006). We next examined the NGF-upregulated phospho-sites and found that significantly more phosphopeptides were upregulated in NGF-treated cells with rat TrkA (361/2,239 [16.8%]) compared to cells with chimeric TrkA (270/2,007 [13.5%]; Figure 4B).…”
Section: Resultssupporting
confidence: 80%
“…The numbers of identified phosphosites were in agreement with previous studies (32,49) and different drug treatments displayed a good reproducibility with a Pearson correlation R in the range of 0.62-0.82 ( Supplementary Fig. S4B and S4C).…”
Section: Quantitative Phosphoproteomics Identifies Functionally Relevsupporting
confidence: 76%
“…Using the Cytoscape STRING app, a network was retrieved for 78 proteins interacting with TrkA (tropomyosin-related kinase A) 10 min after stimulating neuroblastoma cells with NGF (nerve growth factor) (56). With a confidence cutoff of 0.4, the resulting network contains 182 functional associations between 57 of the proteins; the 21 proteins with no associations to other proteins in the network were removed.…”
Section: Cytoscape App Integrationmentioning
confidence: 99%